(untitled) (Economic and Political Thought, 2016)
Norwegian historical, cultural and geopolitical ties with Europe have never been questioned. The fate of this Nordic country, despite the geographical conditions, made it have a unique status of an outsider among friends, i.e. the European Union countries. The close economic and political ties are put into practice mainly in the framework of bilateral agreements and through the structure of the European Free Trade Association. The most important agreement regulating economic relations between Norway and the EU is the Agreement on the European Economic Area, which requires that the country implement the EU legislation concerning the internal market. One should be aware that the status of Norway is mainly determined by the characteristic model of its economy. The country ranks among the richest countries in the world and, what is more important, its prosperity is largely based on export sales of energy resources – which Norway wants to control independently. This is the main reason why the country has not become an official member of the European Union structures. The idea has been rejected in a referendum twice. Norwegians are still very Eurosceptic. Norwegian political approach towards the European Union is often compared to the so-called ‘cherry picking’, which means implementing only the provisions that remain comfortable. However, cooperation is defined as a privileged partnership, and official documents describe Norway as a country integrated with the EU at a rate of 75%.